Strong viral associations with SLE among Filipinos. Issue 1 (28th July 2017) - Vista, Evan S; Weisman, Michael H; Ishimori, Mariko L; Chen, Hua; Bourn, Rebecka L; Bruner, Ben F; Hamijoyo, Laniyati; Tanangunan, Robelle D; Gal, Noga J; Robertson, Julie M; Harley, John B; Guthridge, Joel M; et al.
Abstract : Objectives: Epstein-Barr virus (EBV) is considered an important environmental factor in SLE aetiology, but the relationship between SLE and EBV in the Filipino population is unknown. We tested associations between SLE, lupus-associated autoantibodies and seropositivity for EBV and other herpes viruses in the Filipino population. Methods: Sera from Filipino patients with SLE (n=233), unaffected first-degree relatives (FDRs, n=543) and unrelated controls (n=221) were tested for antibodies against EBV, cytomegalovirus (CMV) and herpes simplex viruses (HSV-1 and HSV-2) by standardised ELISAs. Humoral specificity against EBV nuclear antigen (EBNA)-1 was compared by solid-phase epitope mapping. Autoantibodies were detected by a bead-based multiplex assay. Results were analysed by Fisher's exact test, Student's t-test, χ 2 test and one-way analysis of variance, as appropriate for the question. Results: Filipino patients with SLE had increased seroprevalence and elevated antibody concentrations against EBV viral capsid antigen (EBV-VCA), CMV, HSV-1 and HSV-2 compared with unrelated controls (p<0.05). Seropositivity for anti-EBV early antigen (EA), a marker of EBV reactivation, was dramatically increased in patients with SLE compared with unrelated controls (92.3% vs 40.4%; OR 17.15(95% CI 10.10, 30.66), p<0.0001) or unaffected FDRs (49.4%; OR 12.04(7.42, 20.74), p<0.0001), despite similar seroprevalence of EBV-VCA in patients and FDRs. In patients with SLE, EBV-EA seropositivity correlated with lupus-associated autoantibodies (p<0.001), most notably with autoantibodies against dsDNA, chromatin, Sm, SmRNP and RNP A (p<0.01). Patient and unrelated control sera reacted to the highly repetitive glycine and alanine domain of EBNA-1. An epitope spanning EBNA-1410-420 was identified in sera of patients with SLE and showed limited binding by FDR and control sera. Conclusions: Filipino patients with SLE have elevated prevalence and concentrations of antibodies against EBV, CMV, HSV-1 and HSV-2 antigens, along with altered anti-EBNA-1 specificities. EBV reactivation is more common among Filipino patients with SLE compared with healthy Filipinos and may contribute to SLE pathogenesis in this population.